The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019 8th International Conference on Affective Computing and Intelligent Interaction (ACII) 2019
DOI: 10.1109/acii.2019.8925446
|View full text |Cite
|
Sign up to set email alerts
|

Context in Human Emotion Perception for Automatic Affect Detection: A Survey of Audiovisual Databases

Abstract: An important aspect of human emotion perception is the use of contextual information to understand others' feelings even in situations where their behavior is not very expressive or has an emotionally ambiguous meaning. For technology to successfully detect affect, it must mimic this human ability when analyzing audiovisual input. Databases upon which machine learning algorithms are trained should capture the context of social interactions as well as the behavior expressed in them. However, there is a lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Ideally, data should be annotated without the annotation process influencing the (labelled) data, and collected without the collecting itself influencing the data. The former issue was raised in a recent review by Dudzik et al [87], describing how an annotator (perceiver of the emotion data) can be biased in his or her interpretation of other people's emotions. Regarding the latter issue, an example of the ideal situation could be to search for social media messages related to an event, where the collection itself will not influence the content of these messages.…”
Section: Application Possibilitiesmentioning
confidence: 99%
“…Ideally, data should be annotated without the annotation process influencing the (labelled) data, and collected without the collecting itself influencing the data. The former issue was raised in a recent review by Dudzik et al [87], describing how an annotator (perceiver of the emotion data) can be biased in his or her interpretation of other people's emotions. Regarding the latter issue, an example of the ideal situation could be to search for social media messages related to an event, where the collection itself will not influence the content of these messages.…”
Section: Application Possibilitiesmentioning
confidence: 99%
“…Such information about triggering events has a strong role in interpreting facial behavior [42]. Affective detection work has only tentatively explored this aspect because it is conceptually challenging to translate into automatic systems and generally lacks available corpora for modeling [23].…”
Section: Context In Affect Detectionmentioning
confidence: 99%
“…The insights gained by this act of emotional perspective-taking can complement any information offered by behavior in isolation, thereby enabling an observer to make accurate inferences even for ambiguous cases (e.g., [41]). However, context-sensitive approaches remain under-explored in automatic affect detection [23], despite researchers generally acknowledging their potential [60,66,68]. Likely causes for this neglect are the substantial challenges involved in (1) identifying relevant contextual influences for emotional responses in an application setting, as well as (2) developing technical solutions that provide automatic systems with an awareness of them [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simply speaking, academia is aiming for "in the wild" data collections, meaning, to process information of people even when they are not aware of it. This entails the use of data enriched with additional metadata such as age, sex, profession, socio-demographic information (Dudzik et al, 2019), or specific personality traits (similar to Big Data studies that use freely available data found on the Internet). We consider this type of data (e.g., sex, age, language, proficiency, personality, etc.)…”
Section: Introductionmentioning
confidence: 99%